Efecto de la escarificación química en la calidad de semilla de Centrosema spp. durante el almacenamiento - Búrbano, Edgar A. (Agronomía Mesoamericana, 2016)
One of the most important forage legumes for acid and unfertile tropical soils is Centrosema spp. This genus is characterized by extremely hard seeds. Even with optimum conditions, because of its hard seeds, much does not germinate naturally. With this in mind, three species were selected, C. acutifolium, C. macrocarpum and C. brasilianum to evaluate the effect of chemical scarification on germination and emergence. Also, germination and emergence for these three entries were evaluated after having been stored for nineteen months at 18°C and 50 % relative humidity. Seed counts with and without scarification and the associated interaction with the defined treatments. The results indicated germination was lowered more with Centrosema acutifolium than the others when the described treatments were assessed (germination lowered by 40% after five months of storage). The other two species have harder seed which reflects the limited loss In germination observed (maximum of 10%). The emergence results from field trials were substantially different from germination data obtained in the laboratory (approximately 50%). These results indicate that seed stored under the two treatments for forage species such as Centrosema spp. Did not improve hardening significantly. The controlled conditions favored physiological qualities (germination) while maintaining hardness which was the case for C. macrocarpum. AWN scarified seed should not be stored under non controlled conditions as was noted for C. acutifolium which lost hardness rapidly and lacks defense mechanisms to avoid deterioration while stored. If scarification is employed a few days prior to seeding, adequate storage conditions should be employed.